Supply Chain Management of Agriculture in Azerbaijan: Stages, Analysis and Perspective - Akhmetova, G. T; Nurpeiis, G. S; Apysheva, A.; Shaikhanova, N; Sholpanbaeva, K. G; Sheredko, S.; Grytsevych, D (ExcelingTech, 2020)
Abstract- The article considers economic supply chain management, which involves the intensification of the processing process by deepening the division of labor, the supply chain management of the material and technical base of production, the transformation of scientific and technical progress into productive force and the efficiency of the production management system. The article analyzes the issues of development of clusters in the agricultural sector, especially the supply chain management of the agricultural sector, the role of investments in supply chain management, technical and technological renewal in agricultural supply chain management, as well as improving its structuring in the modernization of the agricultural sector